Propiedades psicométricas del test de principios interacciónales sociopragmáticos en la ciudad de Medellín. (2018)
The main objective of this research was the psychometric properties of the Sociopragmatic Interaction Principles (PIS) test in the context of the city of Medellín, which had been designed by Spencer-Oatey and Jiang (2003) in England and then replicated in China. . A set of six scenarios of daily life among the participants was evaluated.